A new approach in auditing incorporated technology - Yazıcı, Ozan (My University, 2003)
In recent years, increasing volume of transactions in accounting departments, lead the auditors to choose more efficient and effective audit techniques. New audit techniques incorporated technology may improve the effectiveness and efficiency of auditing procedures. The purpose of this study is mainly identifying the technologies that introduce new approaches to auditing and computer assisted auditing tools. Latest developments in Electronic Data Processing (EDP), Information Technologies (IT), Information Systems (IS) and E-commerce operations, auditors faces the problem of expanding their technological knowledge and skills. To accomplish this, audit firms provide their professional staff various technology tools. This study provides guidance on the use of new auditing tools. It also tries to analyze the dependency of personal features like age, sex and education level, title, efficiency, type of audit service, phase of audit and complexity of new audit technologies to adoption of computer assisted auditing tools in Turkish auditing sector. This study suggests that firms investing in computer assisted technology tools should carefully consider the functionality of new types of audit software packages and provide technical trainings for auditors to ensure that the optimal benefit is derived from them.

TEKNOLOJİ İLE BİRLEŞTİRİLMİŞ YENİ BİR DENETİM YAKLAŞIMI Son yıllarda muhasebe departmanlarındaki artan işlem hacmi, denetçileri daha etkin ve kullanışlı teknikler seçmeye yönlendirmiştir. Teknoloji ile birleştirilmiş yeni denetim teknikleri, denetim prosedürlerinin etkinliğini ve kullanışlılığını artırabilir. Bu çalışma, denetime yeni yaklaşımlar getiren teknolojilerin ve bilgisayar destekli denetim tekniklerin tanıtılmasını amaçlamaktadır. Bilgi İşlem Merkezi (BİM), Enformasyon Teknolojileri (IT), Enformasyon Sistemleri (IS) ve İnternet faaliyetlerindeki son gelişmelere bağlı olarak, denetçiler mesleki teknik bilgi ve kabiliyetlerini geliştirme sorunu ile karşı karşıya kalmaktadır. Bu nedenle denetim firmaları, çalışanlarına çeşitli teknolojik araçlar sunmaktadırlar. Bu çalışma yeni denetim tekniklerinin kullanımında yol gösterici niteliktedir. Ayrıca, Türk denetim sektöründe yeni denetim tekniklerinin benimsenmesinde etkili olan yaş, cinsiyet, eğitim gibi kişisel özellikler, ünvan, verimlilik, denetim hizmetinin türü, denetim sahası ve yeni denetim teknolojilerin karmaşıklığı gibi faktörlerin birbirleri ile olan ilişkisinin araştırılması da amaçlanmıştır. Bu çalışma bilgisayar destekli teknolojik araçları kullanan firmaların, denetim sürecine yeni yaklaşımlar getiren yazılım ve teknolojilerin işlevselliğini dikkate almaları ve bu teknolojilerden optimum fayda sağlanabilmesi için çalışanlara teknik eğitim verilmesinin gerekliliğine işaret etmektedir.
Keywords: Muhasebe